THE USE OF ASSEMBLR EDUCATION IN TEACHING MORAL LESSONS AT THE INDONESIAN SCHOOL OF KUALA LUMPUR - Rahmadhani, Eva Kartina; Ahmadi, Ahmadi; Hasyim, Taufiqqurrahman (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
This study examines the use of Assemblr Edu in teaching moral lessons at Sekolah Indonesia Kuala Lumpur, Malaysia. Employing a qualitative case study design, data were gathered through in-depth interviews with teachers and students as well as direct classroom observations to capture authentic learning dynamics. The findings reveal that Assemblr Edu significantly enhances student engagement, motivation, and active participation during lessons. The interactive and immersive features of the application help students visualize abstract moral concepts, thereby deepening their comprehension and fostering reflective thinking. In addition, the use of digital media encourages collaborative learning and provides students with experiences that are more relatable to their daily lives. However, several challenges emerged, including limited technological infrastructure, unequal access to devices, and the need for continuous teacher training to maximize the potential of digital tools. To address these issues, the study recommends improving school facilities, strengthening digital literacy, and providing professional development programs for educators. Overall, the integration of Assemblr Edu demonstrates meaningful progress in utilizing ICT to foster students’ character development, particularly in cultivating moral values within the Indonesian school context abroad.